How do you differentiate #1=e^(xy)/(e^x+xy)#?

Answer 1

#y'=(e^x+y-ye^x-xy^2)/(xe^x+x^2y-x)#

From the given

#1=e^(xy)/(e^x+xy)#
#e^x+xy=e^(xy)#
#d/dx(e^x)+d/dx(xy)=d/dx(e^(xy))#
#e^x*d/dx(x)+x*d/dx(y)+y*d/dx(x)=e^(xy)*[x*d/dx(y)+y*d/dx(x)]#
#e^x+xy'+y*1=e^(xy)*(xy'+y*1)#
#e^x+xy'+y=e^(xy)*(xy'+y)#
#e^x+y-y*e^(xy)=xy'*e^(xy)-xy'#
#e^x+y-y*e^(xy)=(x*e^(xy)-x)y'#
#y'=(e^x+y-y*e^(xy))/(x*e^(xy)-x)#
But, #e^(xy)=e^x+xy#

therefore

#y'=(e^x+y-y*e^(xy))/(x*e^(xy)-x)=(e^x+y-y*(e^x+xy))/(x*(e^x+xy)-x)#
#y'=(e^x+y-ye^x-xy^2)/(xe^x+x^2y-x)#

God bless....I hope the explanation is useful.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To differentiate (1 = \frac{e^{xy}}{e^x + xy}) with respect to (x), apply the quotient rule:

Let (u = e^{xy}) and (v = e^x + xy).

Then, apply the quotient rule:

[ \frac{d}{dx}\left(\frac{u}{v}\right) = \frac{u'v - uv'}{v^2} ]

where (u') and (v') denote the derivatives of (u) and (v) with respect to (x), respectively.

Now, find (u') and (v'):

[ u' = \frac{d}{dx}(e^{xy}) = ye^{xy} ]

[ v' = \frac{d}{dx}(e^x + xy) = e^x + y ]

Substitute these into the quotient rule formula:

[ \frac{d}{dx}\left(\frac{e^{xy}}{e^x + xy}\right) = \frac{(ye^{xy})(e^x + xy) - (e^{xy})(e^x + y)}{(e^x + xy)^2} ]

Simplify this expression as needed.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 3

To differentiate (1 = \frac{e^{xy}}{e^x + xy}), we use the quotient rule. The quotient rule states that for functions (u) and (v), the derivative of (u/v) is given by:

[ \frac{d}{dx}\left(\frac{u}{v}\right) = \frac{v \frac{du}{dx} - u \frac{dv}{dx}}{v^2} ]

In this case, let (u = e^{xy}) and (v = e^x + xy). We find the derivatives (\frac{du}{dx}) and (\frac{dv}{dx}):

[ \frac{du}{dx} = \frac{d}{dx}(e^{xy}) = e^{xy} \cdot \frac{d(xy)}{dx} = ye^{xy} ]

[ \frac{dv}{dx} = \frac{d}{dx}(e^x + xy) = e^x + y ]

Now, apply the quotient rule to find (\frac{d}{dx}\left(\frac{e^{xy}}{e^x + xy}\right)):

[ \frac{d}{dx}\left(\frac{e^{xy}}{e^x + xy}\right) = \frac{(e^x + xy)(ye^{xy}) - e^{xy}(e^x + y)}{(e^x + xy)^2} ]

Simplify the numerator:

[ = \frac{ye^{xy}(e^x + xy) - e^{xy}(e^x + y)}{(e^x + xy)^2} ]

Expand and rearrange terms:

[ = \frac{ye^{x + xy^2} - e^x e^{xy} - e^{xy}y}{(e^x + xy)^2} ]

So, the derivative of (1 = \frac{e^{xy}}{e^x + xy}) with respect to (x) is:

[ \frac{ye^{x + xy^2} - e^x e^{xy} - e^{xy}y}{(e^x + xy)^2} ]

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7